1997
DOI: 10.1002/j.1550-8528.1997.tb00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Parity‐Associated Body Weight: Modification by Sociodemographic and Behavioral Factors

Abstract: This research examines the association between parity and body weight and how this relationship is modified by sociodemographic and behavioral factors. Using multiple linear regression analysis, the study assessed the relationship between parity and relative body weight (as Body Mass Index, BMI) and how this relationship interacts with seven sociodemographic and seven behavioral factors in a national sample of 5,707 women from the Second National Health and Nutrition Examination (NHANES 11) survey. After adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 25 publications
4
34
1
Order By: Relevance
“…Moreover, US women at greatest risk of weight gain are those with an education below college level, newly weds and those with a very low family income 37 , while marital status did not have significant effects on obesity among younger women 38 . On the other hand, the amount of weight gain associated with parity was greater in married than unmarried women, and less in those who were active outside of recreation versus those who were less active 39 . All these observations are in good agreement with the results obtained in this EU study.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, US women at greatest risk of weight gain are those with an education below college level, newly weds and those with a very low family income 37 , while marital status did not have significant effects on obesity among younger women 38 . On the other hand, the amount of weight gain associated with parity was greater in married than unmarried women, and less in those who were active outside of recreation versus those who were less active 39 . All these observations are in good agreement with the results obtained in this EU study.…”
Section: Discussionmentioning
confidence: 88%
“…Reproductive factors are a plausible explanation for this gender difference in the association between short stature and obesity. Parity has been positively associated with weight gain and with the onset of obesity in population-based studies in developed countries (11)(12)(13)(14)(15)(16), and also in Brazil, as shown by a previous analysis of the III Brazilian Demographic and Health Survey (DHS-96) (17). Events during the fetal and early postnatal growth period by causing permanent metabolic alterations through adult life may facilitate maternal fat deposition during pregnancy.…”
Section: Introductionmentioning
confidence: 92%
“…(Weight changes of nonpregnant women are further discussed in the NP=NL section.) Pregnancy-related weight gain may be modified by sociodemographic and behavioural factors such as race, employment status, cigarette smoking and recreational exercise (Wolfe et al, 1997). It is likely that genetic factors may play an important role in pregnancy-related weight gain for some women, although little is known about genetic susceptibility to the development of obesity specifically during the reproductive period.…”
Section: Change In Mns During Pregnancy In Affluent Societiesmentioning
confidence: 99%
“…However, cross-sectional studies of age=parity and women's weight have most commonly found positive associations (Brown et al, 1992;Farahati et al, 1993;Rush et al, 1996;. Still, these associations are modified by sociodemographic and behavioural factors: the amount of weight associated with parity is higher for black women than white women, higher for nonsmokers than smokers, and higher in those with low levels of recreational exercise (Wolfe et al, 1997). Some investigators have reported parity to be associated with centralization of body fat distribution, independent of relative weight per se (Björkelund et al, 1996).…”
Section: Age and Paritymentioning
confidence: 99%